TanDEM-X Performance Analysis - Huber, Sigurd; Younis, Marwan; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurement) is a space borne earth observation mis-sion with the goal of generating a global Digital Elevation Model (DEM) with an unprecedented accuracy corre-sponding to the HRTI-3 specifications. TanDEM-X will fly in a special orbit formation (HELIX formation) with the fully compatible TerraSAR-X (TSX-1) satellite in order to collect interferometric SAR data. It is planned to cover the earth surface twice with different baselines, in order to ease phase unwrapping. Within a mission dura-tion of only three years, data for a global HRTI-3 DEM shall be acquired. The paper is divided into two parts. Starting with the TanDEM-X mission objective, the height performance model is presented, taking into account several error sources, like thermal decorrelation, quantization errors, range- and azimuth-ambiguities, misregistration as well as volume decorrelation. The analysis is extended to dif-ferent terrain-types, showing a significant impact on the height accuracy. Based on a global terrain classification map, a first rough estimate of the global DEM performance is given. The second part concentrates on an analysis of the impact of the block adaptive quantiser (BAQ) in terrain with high dynamic range in backscatter power (e.g. urban areas). Simulation results based on TerraSAR-X measure-ment data will be presented.
DLR Import::2019-04-03